2016
DOI: 10.1534/genetics.116.188821
|View full text |Cite
|
Sign up to set email alerts
|

Limits to Adaptation in Partially Selfing Species

Abstract: In outcrossing populations, "Haldane's sieve" states that recessive beneficial alleles are less likely to fix than dominant ones, because they are less exposed to selection when rare. In contrast, selfing organisms are not subject to Haldane's sieve and are more likely to fix recessive types than outcrossers, as selfing rapidly creates homozygotes, increasing overall selection acting on mutations. However, longer homozygous tracts in selfers also reduce the ability of recombination to create new genotypes. It … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 80 publications
3
63
0
Order By: Relevance
“…In an initially outcrossing population exposed to regular selfing, purging is therefore expected to slow down as the recessive semi‐lethals are eliminated and the small‐effect alleles persist. Their persistence may also be facilitated by the decrease in the effective size due to both homozygosity and selective interferences under self‐fertilization (Hartfield and Glemin ), which is confirmed here by the lower genetic diversity of the S lines compared to all others. This persistence might explain that inbreeding depression still persisted at G50.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In an initially outcrossing population exposed to regular selfing, purging is therefore expected to slow down as the recessive semi‐lethals are eliminated and the small‐effect alleles persist. Their persistence may also be facilitated by the decrease in the effective size due to both homozygosity and selective interferences under self‐fertilization (Hartfield and Glemin ), which is confirmed here by the lower genetic diversity of the S lines compared to all others. This persistence might explain that inbreeding depression still persisted at G50.…”
Section: Discussionsupporting
confidence: 76%
“…However, it is not clear whether purging by inbreeding would be efficient at preventing decreases in population fitness over a larger number of generations and with higher selfing rates (i.e., nearly obligate selfing instead of the average selfing rate of 50% we imposed). Selective interference and reduced effective size may eventually limit the efficiency of purging (and of selection in general) in predominant selfers (Lande and Porcher ; Hartfield and Glemin ; Noël et al. ), making them evolutionary dead‐ends (Goldberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lower genetic diversity of self‐fertilizing populations, it has been suggested that they should be less able to adapt to a changing environment (e.g., Stebbins ; Williams ; Takebayashi and Morrell ). In the absence of epistasis, existing models indeed predict that selfing populations should have lower rates of adaptation than outcrossing ones (Glémin and Ronfort ; Hartfield and Glémin ). When compensatory effects between mutations are possible, however, a substantial amount of genetic variance may be hidden by genetic associations between loci in highly selfing populations (Lande and Porcher , the present study).…”
Section: Discussionmentioning
confidence: 99%
“…When loci are tightly linked, the effective rate of recombination and effective population size are significantly reduced, even in populations with rs not very close to 1, rendering selection against deleterious alleles ineffective (Kamran‐Disfani and Agrawal ). By the same token, linkage generates Hill–Robertson interference between adaptive alleles, which reduces the advantage selfers experience during adaptation from co‐dominant or even mildly recessive alleles (Hartfield and Glémin ). Finally, linkage increases hitchhiking of deleterious variants with adaptive alleles, especially in highly selfing populations, which reduces the fixation probability of even slightly recessive adaptive alleles (Hartfield and Glémin ; Kamran‐Disfani and Agrawal ).…”
Section: Discussionmentioning
confidence: 99%